THE SELECTION PHASE AS THE ALPHA OF THE MANAGEMENT SYSTEM FOR MEDICINES AND CONSUMABLE MEDICAL SUPPLIES IN HOSPITALS - Muttaqin Muttaqin; Andi Selvi Kartini Wonsu; Andi Widyawati; Deasy Mauliana; Ayu Indira (Jurnal Administrasi Negara, 2025)
Selection constitutes the initial stage (Alpha) of an efficient, effective, accountable, and sustainable management process for medicines and consumable medical supplies (CMS) in hospitals. This article details the selection phase that precedes the planning phase as part of the overall management process for medicines and CMS at La Mappapenning Hospital. The data was gathered through observation, interviews, and documentation of medicine and CMS management practices. Data analysis followed an interactive model: data collection, data condensation, data presentation, and verification/conclusion. The results indicate that the selection of medicines and CMS is carried out in an efficient, effective, accountable, and sustainable manner, serving as the alpha process or management system at La Mappapenning Hospital. Medicines and CMS are selected prior to procurement planning, based on proposals from users and reference to the national formulary, while considering their efficacy, safety, quality, and cost. The selection process involves medical staff, pharmacists, and employees from related management units. The outcome of this selection serves as the input for the medicine and CMS planning phase, which is regularly updated based on utilization evaluation at La Mappapenning Regional General Hospital in Bone Regency.